PEDAGOGY OF PARTNERSHIP IN THE SPIRITUAL EDUCATION OF STUDENTS OF NEW UKRAINIAN SCHOOL IN MOUNTAINOUS REGIONS - Kopchuk-Kashetska, Maria; Dovgij, Oleg; Klepar, Maria (Mountain School of Ukrainian Carpaty, 2021)
The article actualizes the problem of realization of ideas of pedagogy of partnerships in the spiritual education of students of the New Ukrainian School of mountainous region. The essence of the concepts “pedagogy of partnership”, “spiritual education”, ”moral and spiritual values” are revealed. It is noted that the concept of the New Ukrainian School is the first document of reform, which identified the main principles of new education. The principles pedagogy of partnership is based on are presented, according to the Concept of “New Ukrainian School”. It was found that at the present stage of creation of Ukraine as a democratic constitutional state and its integration into the European community the problem of pedagogy of partnership of primary school students becomes more important. Students, parents and teachers, united by common goals and aspirations are voluntary and interested accomplices, equal participants in the educational process, responsible for the result. The teacher is a child's friend, and the family is involved in building it educational trajectory. This encourages the use of New Ukrainian School in the educational process, cultural and pedagogical heritage of the Ukrainian people, finding the best ways of moral and spiritual education of schoolchildren on the basis of revival of folk customs and traditions. It is proved that the centuries-old experience of the Ukrainian people, its ideals, notions of good and evil have a significant impact on the formation of moral spiritual values of schoolchildren. It is concluded that the pedagogy of partnership is a true democratic way of cooperation between teachers, students and their parents, provides unconditional equality in the right to respect, trust and mutual demanding in spiritual education.